2020
DOI: 10.3389/fpsyt.2020.00056
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural White Matter and Links With Subcortical Structures in Chronic Schizophrenia: A Free-Water Imaging Approach

Abstract: system in patients with chronic schizophrenia and schizoaffective disorder. Findings warrant replication in larger samples.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…Besides the high Cohen's d effect size estimate, we found no significant association of regional FA with either current or cumulative antipsychotic exposure. These null-findings in line with previous studies in EOP patients [12,[18][19][20][21] and studies in adult-onset psychosis [5,22]. For instance, studying white matter microstructure in 1,963 patients with schizophrenia, Kelly and colleagues found no significant effect of medication PLOS ONE dosage [5].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Besides the high Cohen's d effect size estimate, we found no significant association of regional FA with either current or cumulative antipsychotic exposure. These null-findings in line with previous studies in EOP patients [12,[18][19][20][21] and studies in adult-onset psychosis [5,22]. For instance, studying white matter microstructure in 1,963 patients with schizophrenia, Kelly and colleagues found no significant effect of medication PLOS ONE dosage [5].…”
Section: Discussionsupporting
confidence: 78%
“…As the consistency of DWI metrics seems affected by brain edema and inflammatory response, future studies can benefit from using tools such as free water imaging. Free-water imaging separates the contribution of extracellular water from the diffusion measure, leading to a higher specificity in detecting microstructural changes [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there were insufficient data to investigate the association between FW values and PANSS subscales, one study [ 25 ] reported a secondary analysis revealing patients with positive symptoms (olfactory hallucinations, thought disorder, pressured speech, and inappropriate affect) had significantly higher FW values relative to patients who were asymptomatic. One other study [ 32 ] also showed that total Scale for the Assessment of Positive Symptoms scores were significantly associated with increased FW values in the right posterior thalamic radiatia and the left sagittal stratum.…”
Section: Resultsmentioning
confidence: 91%
“…On the one hand, some studies indicated that WM integrity may be affected by the type of medication or illness duration (Ozcelik-Eroglu et al, 2014;Samartzis et al, 2014). On the other hand, the recent studies on big-sample sizes revealed that the dose of medication (calculated as the chlorpromazine equivalent) did not affect the diffusivity parameters of WM (Kelly et al, 2018;Koshiyama, 2020;Joo et al, 2020;Gurholt et al, 2020).…”
Section: Discussionmentioning
confidence: 99%